Cationic dye adsorption on the bioadsorbents based on chitosan and sodium alginate-iron oxide nanoparticles: Kinetic, isotherm and thermodynamic studies - Kamaci, Umran Duru; Kamaci, Musa (ELSEVIER, 2025)
Herein, we fabricated a series of bioadsorbents based on chitosan and sodium alginate-iron oxide nanoparticles for the adsorption of methylene blue. As known, iron nanoparticle-based bioadsorbents have exhibited outstanding adsorption behavior while chitosan has been shown low adsorption due to its low surface area. For this reason, we aimed to increase the chitosan s surface area and dye adsorption behavior by mixing it with sodium alginate and iron nanoparticles. Some characterization techniques such as Fourier Transform-Infrared Spectroscopy (FT-IR), X-ray diffraction (XRD), Scanning Electron Microscopy (SEM), Brunauer-Emmett-Teller (BET), and thermogravimetric (TG) analysis were used to confirm the structure of bioadsorbents and to investigate crystalline, surface, and thermal properties. The adsorption of methylene blue onto the bioadsorbents was fitted to pseudo-second order kinetic and Langmuir isotherm models. The maximum methylene blue adsorption capacity was found between 162.77 and 212.77 mg/g. Moreover, thermodynamic parameters such as change in free energy (Delta Go, in the range from -4. 524 to -0.748 kJ/mol), change in enthalpy (Delta Ho, in the range from -31.100 to -28.894 kJ/mol), and change in entropy (Delta So, in the range from -90.963 to -84.454 kJ mol- 1 K- 1) were calculated with negative values. The findings from the thermodynamic studies indicated that the adsorption process was spontaneous and exothermic.
Keywords: Nanoparticles; Methylene blue; Iron oxide; Adsorption; Chitosan; METHYLENE-BLUE; REMOVAL; ACID; Chemistry